Development of a measure of mental health stigma including police behaviors. Issue 4 (4th July 2019) - Yasuhara, Kento; Formon, Dana L.; Phillips, Sarah; Yenne, Elise M.
Abstract : Various stigmatizing notions are associated with mental illness, resulting in negative personal (e.g. employment discrimination) and societal (e.g. public treatment of the mentally ill as 'dangerous' and/or 'criminal') outcomes. This study develops and validates a new multi-scale assessment tool to assess several dimensions of mental illness stigma, including perceived dangerousness, self-care, social distance, treatment amenability and predicted police behavior. A total of 641 undergraduate students from various American universities completed the new stigma measure along with two other existing measures. The results indicate that the new stigma measure has an acceptable three-factor solution consisting of self-care, dangerousness and police behavior. The self-care and dangerousness factors were found to have concurrent validity with the corresponding scales of the existing measures. Future research involving different populations, as well as the policy implications of the new police behavior factor, are discussed.